(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Insider trading in India is a key capital market issue which has been regulated by SEBI as per the provisions of the Prohibition of Insider Trading Regulation, 2015. In fact, this subject involves lots of fundamental aspects of finance and capital market issues. It is essential to study the subject in detail by analysing the existing law and precedents in India. The present study aims to analyse the insider trading laws in India, one of the world’s largest emerging capital markets and insider trading laws in the United States of America, the world’s largest capital market.